The geographic knowledge of non-literate social strata in Athens and Rome (5th century BCE – 2nd century CE) - de Aquino Silva, Guilherme (Romanitas - Revista de Estudos Grecolatinos, 2023)
The book Illiterate Geography in Classical Athens and Rome, authored by Daniela Dueck (2021), fills a gap in the historiography of ancient geography. It not only compiles non-textual sources but also turns its attention to the illiterate social strata, seeking to identify how geographical knowledge was produced and disseminated among those who lacked the privilege of formal education. Consequently, the work plays a crucial role in shifting the focus away from texts produced by the literate elite, which have been extensively explored by historians, and instead, proposes an examination of the masses. Thus, we recommend this book to those interested in understanding the relationship of the literat and illiterate Greeks and Romans with Geography.